Public Value of "Anak Itah" Program Innovation in Palangka Raya City - Yopiannor, Farid Zaky; Milka, Milka (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
Excellent public service is very important in the new normal life, especially inÂ Palangka Raya City. The purpose of this study is to describe the public value ofÂ â€œAnak Itahâ€ program. This program is an innovation of public serviceÂ presented by the Regional Population and Civil Registry Office of PalangkaÂ Raya City. This innovation is a priority birth certificate service for people whoÂ give baby birth in hospitals that cooperate with the office. For those givenÂ priority 3-in-1 service (birth certificate, family card, and child identity card)Â directly at the hospital. Philosophically the word â€œAnak Itahâ€ is derived fromÂ the Dayak Language which means â€˜Our Childrenâ€™. This study uses the publicÂ value concept as an analysis tool using qualitative methods throughÂ interviews, observation, and documentation as the data collection. The studyÂ results show that the performance implementation of â€œAnak Itahâ€ programÂ provides ease and efficiency of time to the public as users. They provide aÂ positive response and the program is relevant to their needs in the context ofÂ public service in the post-pandemic era Â 